2007
DOI: 10.1063/1.2435704
|View full text |Cite
|
Sign up to set email alerts
|

Mode-coupling of low-frequency electromagnetic waves in dusty plasmas with temperature anisotropy

Abstract: This paper studies the effects of the presence of dust particles with variable charge, in fully ionized, homogeneous, magnetized plasma of electrons and ions, with the electrons and ions described by bi-Maxwellian distributions in the equilibrium. The dispersion relation and the absorption rate are obtained for low frequency waves, with frequencies much lower than the ion cyclotron frequency. Two branches are obtained, identified as the whistler branch and the branch of circularly polarized waves, featuring da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In other words, we replace the functions ν βd 0 ( v ) by the expressions for ν βd given by . The approximation employed here is validated by a recent study performed by de Juli et al [2007a] that demonstrated, for a purely Maxwellian plasma, that in the Alfvén wave frequency range both the real and imaginary parts of the dispersion relation can be satisfyingly described by the average collision frequency approximation. We believe that the same approximation is still valid for the case of a superthermal electron population, although further study is needed to completely justify this assertion.…”
Section: Dispersion Relation For Parallel‐propagating Alfvén Wavesmentioning
confidence: 77%
See 1 more Smart Citation
“…In other words, we replace the functions ν βd 0 ( v ) by the expressions for ν βd given by . The approximation employed here is validated by a recent study performed by de Juli et al [2007a] that demonstrated, for a purely Maxwellian plasma, that in the Alfvén wave frequency range both the real and imaginary parts of the dispersion relation can be satisfyingly described by the average collision frequency approximation. We believe that the same approximation is still valid for the case of a superthermal electron population, although further study is needed to completely justify this assertion.…”
Section: Dispersion Relation For Parallel‐propagating Alfvén Wavesmentioning
confidence: 77%
“…In particular, the absorption rates are increased and several couplings between distinct branches of the dispersion relation appear, both features related to the variation of the dust electric charge. The growth rate of instabilities appearing in anisotropic plasmas can also be affected by the presence of the dust [ de Juli et al , 2007a, 2007b]. More recently, Gaelzer et al [2009] studied how KAWs propagating in the oblique direction in a Maxwellian plasma are affected by the dust and found that not only are the absorption rates enhanced in comparison with the dustless limit, but the refractive properties of the long‐wavelength, oblique Alfvén waves are also significantly altered.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are an early paper by Rosenberg [36], which contains a study of instabilities of ion-acoustic waves produced by current in a fully ionized collisionless dusty plasma, without taking into account the effect of variations of the dust charge, a more recent investigation of the effect of dust-charge variation on high-frequency electrostatic plasma waves [37], and several studies on low-frequency electromagnetic waves [38][39][40][41][42][43] and on electrostatic waves in dusty plasmas [44][45][46] in which some of us have been engaged, which also take into account the effect of dust-charge variation, incorporating the dependence on the frequency of inelastic collisions of plasma electrons and ions with the dust particles into the components of the dielectric tensor. It may be added that the kinetic formulation employed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings correspond to those obtained in the case of anisotropic Maxwellian distributions, for which the mode coupling between circularly polarized and whistler branches was observed to remain when parallel temperature is larger than perpendicular temperature, and disappear when perpendicular temperature becomes sufficiently larger than parallel temperature. 36 The objective of the paper has been to investigate the dependency of the dispersion relation on the parameters j k and j ? , and on the presence of the dust.…”
Section: Final Remarksmentioning
confidence: 99%
“…33 In particular, in the case of Alfv en waves in spacelike conditions, for instance, we have already discussed the modification of damping due to collisional charging of dust particles, 34 and the occurrence of mode coupling between the whistler and the ion cyclotron branch. 35,36 These analysis have been made for the case of Maxwellian distributions for ions and electrons. More recently, we have explored the combined effect of the non-Maxwellian features of kappa distributions and the presence of dust, combination which originate considerable modifications in the dispersion relation for Alfv en waves.…”
Section: Introductionmentioning
confidence: 99%